Pengaruh Pemberian Jus Semangka, Jus Belimbing, Dan Campuran Jus Semangka Belimbing Terhadap Tekanan Darah Pada Lansia Hipertensi Di Banjar Datengan Desa Tumbakbayuh Kecamatan Mengwi Kabupaten Badung - Rosinta, Ni Putu Yuhana (Indonesian Academia Health Sciences Journal, 2020)
Objective:  Hypertension is a condition of the human body that has a systolic blood pressure greater than or equal to 140 mmHg and a diastolic blood pressure greater than or equal to 90 mmHg. In Indonesia in 2007 one of three people (31.7%) who were over 18 years old suffered from hypertension. In Banjar Datengan there are 57 elderly people and 35 of them suffer from hypertension. This study aimed to determine the effect of watermelon juice, starfruit juice and mixed watermelon and starfruit juice on blood pressure in elderly hypertension in Banjar Datengan, Tumbakbayuh Village, Mengwi District, Badung Regency.Methods:  The design of this study was True Experiments with a sample of 33 people selected through simple random sampling technique. The instrument used was sphygmomanometer and observation sheet, the results of blood pressure were then analyzed using One Way Anova statistical test followed by the LSD (Least Significant Differencetest) test.Results:  The mean systolic and diastolic blood pressure (pre test) showed no significant difference (p> 0.05). After treatment (post test) the mean systolic and diastolic blood pressure showed a significant difference (p <0.05). The LSD test between the three groups showed no significant difference (p> 0.05).Conclusion:  From the results of this study it can be concluded that watermelon juice , starfruit juice and a mixed of starfruit and watermelon juice can reduce systolic and diastolic blood pressure.